Na teoria e na ficção: a vanguarda em Clarice Lispector - Malavolta Pinho, Marília Gabriela [UNESP]; Marchezan, Luiz Gonzaga [UNESP] (My University, 2014)
The short story “Os desastres de Sofia” (1964), of Clarice Lispector, can be read as fictional metaphor for the way as the writer elaborated and presented the concept of “Vanguard”. Philosophical reflections of Walter Benjamin (1933) contains the arguments that Clarice, in this narrative, invigorates, by the use of modern keys, vanguardist, according to her conception, which Benjamin sanctioned by the melancholic look of the past. Clarice is notable as a writer of prose affiliated with the brazilian modern poetry.

O conto “Os desastres de Sofia” (1964), de Clarice Lispector, pode ser lido como metáfora ficcional da maneira como a escritora elaborou e apresentou o conceito de “Vanguarda”. Reflexões filosóficas de Walter Benjamin (1933) contêm os argumentos que Clarice, no enredo desse conto, revigora, trazendo em chaves modernas, vanguardistas, segundo sua concepção, o que Benjamin sancionou pelo olhar melancólico do passado. Assim, Clarice se faz notar como escritora de uma prosa (poética) conscientemente filiada à tradição da poesia brasileira moderna.
Keywords: Clarice Lispector; Walter Benjamin; Vanguard; Modernism; Modernity; Literatura Brasileira-Prosa-Poesia